2012
DOI: 10.1002/app.35642
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of cellulose nanofibers from para rubberwood and their reinforcing effect in poly(vinyl alcohol) composites

Abstract: In this article, we present an efficient method for isolating cellulose nanofibers from para rubberwood sawdust with a combination of chemical, mechanical, and ultrasonic treatments. The effects of the alkali concentration and treatment pathway on the cellulose structure and properties are discussed. The reinforcing efficiency of the resulting fibers on poly(vinyl alcohol) (PVA) composites was characterized. Field emission scanning electron microscopy and atomic force microscopy results revealed a well-organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…The strong band at 1245 cm À1 is assigned to the ester acetate CAO bending mode and other peaks located at 1413 cm À1 , assigned to the symmetric (ms.) stretching vibration of the ACOOA group, and 1092 cm À1 , due to CAO stretching can be found related to PVA 51,52. A broad band observed from 3200 to 3550 cm À1 in the PVA spectra corresponding to the hydroxyls (AOH) stretching due to the strong hydrogen bond of intramolecular and intermolecular type, which indicate the presence of hydroxyl groups.…”
mentioning
confidence: 89%
“…The strong band at 1245 cm À1 is assigned to the ester acetate CAO bending mode and other peaks located at 1413 cm À1 , assigned to the symmetric (ms.) stretching vibration of the ACOOA group, and 1092 cm À1 , due to CAO stretching can be found related to PVA 51,52. A broad band observed from 3200 to 3550 cm À1 in the PVA spectra corresponding to the hydroxyls (AOH) stretching due to the strong hydrogen bond of intramolecular and intermolecular type, which indicate the presence of hydroxyl groups.…”
mentioning
confidence: 89%
“…The reported 10 wt% cellulose nanofiber/PVA composite presented an increase in Young's modulus from 45 MPa to 120 MPa [10]. Thus, it was confirmed that the cellulose nanofibers were promising materials for the reinforcement of polymers, and continuous and enormous efforts have been made to isolate cellulose nanofibers.…”
Section: Introductionmentioning
confidence: 73%
“…PVA powder was dissolved in distilled water and stirred at 95°C for 3 hours to produce 5 wt% PVA solution [10] with high transparency. Cel-F suspension was then mixed to the 5 wt% PVA solution and stirred for 1 hour.…”
Section: Fabrications Of Cel-f/pva Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, however, known to be quite challenging to extract cellulose nanofibers from original cellulose beads because of the strong interfacial interactions functioning between cellulose molecular chains due to hydrogen bondings. Therefore, nanofabrication processes of cellulose generally have multiple processing steps which occasionally required the use of toxic solvents or catalysts [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%